Prokrastinasi akademik ditinjau dari conscientiousness pada mahasiswa Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia - Jason Kosasi; Nurmaizar Nilawati Siregar; Rianda Elvinawanty (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2019)
This study aims to find the relationship between conscientiousness and academic procrastination. The hypothesis of this study states that there is a negative correlation between conscientiousness and academic procrastination, assuming that the higher the conscientiousness, the lower the academic procrastination will be and conversely. The subjects of this study were 97 students from Faculty of Technology and Computer Science. The calculation was performed by testing requirements analysis (assumption test), which consists of normality test for distribution and linearity test for relationships. Product Moment correlation with SPSS 17 for windows was used in the data analysis. The results in the data analysis showed that the correlation coefficient was -0.541 with p 0.000 (p0.05). It shows that there is a negative correlation between conscientiousness and academic procrastination. From these results, it is concluded that the hypothesis stating there is a negative correlation between conscientiousness and academic procrastination is acceptable.